A systematic review of the quality and scope of economic evaluations in child oral health research - H. J. Rogers; H. D. Rodd; J. H. Vermaire; K. Stevens; R. Knapp; S. El Yousfi; Z. Marshman (BMC, 2019)
Abstract Background Economic evaluations provide policy makers with information to facilitate efficient resource allocation. To date, the quality and scope of economic evaluations in the field of child oral health has not been evaluated. Furthermore, whilst the involvement of children in research has been actively encouraged in recent years, the success of this movement in dental health economics has not yet been explored. This review aimed to determine the quality and scope of published economic evaluations applied to children's oral health and to consider the extent of children's involvement. Methods The following databases were searched: CINAHL, Cochrane Library, Econlit, EThOS, MEDLINE, NHS EED, OpenGrey, Scopus, Web of Science. Full economic evaluations, relating to any aspect of child oral health, published after 1997 were included and appraised against the Drummond checklist and the Consolidated Health Economic Evaluation Reporting Standards by a team of four calibrated reviewers. Data were also extracted regarding children's involvement and the outcome measures used. Results Two thousand seven hundred fifteen studies were identified, of which 46 met the inclusion criteria. The majority (n = 38, 82%) were cost-effectiveness studies, with most focusing on the prevention or management of dental caries (n = 42, 91%). One study quantified outcomes in Quality Adjusted Life Years (QALYs), and one study utilised a child-reported outcome measure. The mean percentage of applicable Drummond checklist criteria met by the studies in this review was 48% (median = 50%, range = 0-100%) with key methodological weaknesses noted in relation to discounting of costs and outcomes. The mean percentage of applicable CHEERS criteria met by each study was 77% (median = 83%, range = 33-100%), with limited reporting of conflicts of interest. Children's engagement was largely overlooked. Conclusions There is a paucity of high-quality economic evaluations in the field of child oral health. This deficiency could be addressed through the endorsement of standardised economic evaluation guidelines by dental journals. The development of a child-centred utility measure for use in paediatric oral health would enable researchers to quantify outcomes in terms of quality adjusted life years (QALYs) whilst promoting child-centred research.